A preliminary assessment of the hydrodynamics of the Touw River and Wilderness Lakes system with emphasis on the management of the estuary mouth - Donald, Ian R. (Stellenbosch : Stellenbosch University, 2013)
Thesis (MEng)--Stellenbosch University, 2013.